2013
DOI: 10.1016/j.ghir.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone treatment in adults with Prader–Willi syndrome

Abstract: Objective Since limited data exist on adults with Prader-Willi syndrome (PWS) and growth hormone (GH) treatment, we report our experience on the effects of treatment for one year on body composition, physical activity, strength and energy expenditure, diet, general chemistry and endocrine data with quality of life measures. Design We studied 11 adults with PWS (6F:5M; average age = 32 yrs) over a 2 year period with GH treatment during the first year only. Electrolytes, IGF-I, glucose, thyroid, insulin, lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 40 publications
(36 reference statements)
4
60
2
1
Order By: Relevance
“…Previously published studies have reported some effect on LDL and HDLcholesterol levels during GH treatment (6,(12)(13)(14)(15)(16)(17)(18)(19). In the present study, four of the patients were obese and, in accordance with other studies, only two patients had slight dyslipidaemia, with the exception of the patient with familiar hypercholesterolaemia.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previously published studies have reported some effect on LDL and HDLcholesterol levels during GH treatment (6,(12)(13)(14)(15)(16)(17)(18)(19). In the present study, four of the patients were obese and, in accordance with other studies, only two patients had slight dyslipidaemia, with the exception of the patient with familiar hypercholesterolaemia.…”
Section: Discussionsupporting
confidence: 90%
“…The total duration of GH therapy was similar in the two groups, but the duration of GH therapy during adulthood was longer if GH treatment had been initiated during adulthood. This is readily explained by the fact, that the initial studies on the efficacy of GH treatment in adult PWS patients were undertaken on patients who first received treatment as adults (14)(15)(16). The continuation of GH treatment initiated during childhood did not become usual clinical practice until later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most individuals with PWS, but not all, are deficient in GH and studies that were initially focused on improving growth have not only demonstrated this effect, but also improvements in metabolism, body composition, behavior and cognition (38)(39)(40)(41)(42)(43)(44). However, GH therapy on occasion can be associated with significant side effects, such as the stimulation of adenoid tissue leading to obstructive sleep apnea so it should be used carefully in the treatment of PWS.…”
Section: Clinicaltrialsgov [Nct]: Id Number Nct01725152)mentioning
confidence: 99%
“…The analyzed studies were divided into studies of 12 month duration and studies of 24-72 months duration and the beneficial effects on body composition were found in all studies. Furthermore, a study of 11 adults with PWS was published recently also reporting beneficial effects on body composition [34].…”
Section: Gh Treatment In the Transition Period In Pwsmentioning
confidence: 99%